2020
DOI: 10.1088/1755-1315/408/1/012080
|View full text |Cite
|
Sign up to set email alerts
|

Micrococcus luteus and Serratia marcescens, as a new association of bio-agents for microbial fuel cells

Abstract: Microbial fuel cells make it possible to generate electricity by eliminating and using wastewater components. For these purposes, the most viable microbial associations in microbial fuel cells. The presence of strains of different microorganisms allows you to consume a much wider range of compounds. Multicomponent makes them more resistant to the negative effects of stressful environmental factors. An example of such associations are silt sediments of biological treatment plants. The purpose of this work was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Previous studies on the same inoculum reported that the voltage generated with B. subtilis was only 150 mV under the 1 kΩ external load using glucose as substrate 26 . Furthermore, the voltage generation by S. marcescens from activated sludge as inoculum was only 9 mV in MFC 27 …”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Previous studies on the same inoculum reported that the voltage generated with B. subtilis was only 150 mV under the 1 kΩ external load using glucose as substrate 26 . Furthermore, the voltage generation by S. marcescens from activated sludge as inoculum was only 9 mV in MFC 27 …”
Section: Resultsmentioning
confidence: 85%
“…26 Furthermore, the voltage generation by S. marcescens from activated sludge as inoculum was only 9 mV in MFC. 27 Interestingly, BTEP concentrations in all MFCs decreased to below 70 mg/L and removal efficiency approached to 97.8%, 99.5%, 99.9%, and 93.7% for BTEP, respectively, with co-substrate-fed MFCs, indicating that the most BTEP was consumed by diverse non-ARB that cannot produce electricity. The respective BTEP removal efficiency of BTEP-fed MFC was 97.6%, 99.3%, 98.8%, and 95.4%, but lower voltage was generated.…”
Section: Effect Of Co-substrate On Mfc Performancementioning
confidence: 89%
“…The highest efficiency of substrate removal (48%) was also obtained when using MFC with an applied voltage of 0.5V. This was followed by 0.3V (37%), 0.1V (32%) and control (27%) [8][9].…”
Section: Discussionmentioning
confidence: 85%
“…Ранее он был выделен нами из активного ила очистных сооружений нефтеперерабатывающего предприятия. Штамм продемонстрировал довольно высокую электрогенную активность в МТЭ [24,25]. Он депонирован во Всероссийскую коллекцию микроорганизмов (ВКМ) под номером ВКМ Ac-2637 D.…”
Section: экспериментальная часть бактерии объектом исследования являл...unclassified